André Wessels, A century of postgraduate Anglo-Boer War (1899-1902) studies: Masters’ and doctoral studies completed at universities in South Africa, in English-speaking countries and on the European Continent, 1908-2008: book review - Ferreira, O. J. O. (Faculty of the Humanities, University of the Free State, 2011)
Abstract not available
André Wessels, A century of postgraduate Anglo-Boer War (1899-1902) studies: Masters’ and doctoral studies completed at universities in South Africa, in English-speaking countries and on the European Continent, 1908-2008. Bloemfontein: SUN PReSS, 2010. ISBN: 978-1-920383-09-1, Softcover, 205 pages
Keywords: Wessels, André; Book review